Lembaga Pelabuhan Johor (LPJ) / Anis Raihana Amirnesam - Amirnesam, Anis Raihana (Universiti Teknologi MARA, Perlis, 2024)
This internship report explained the work experience and activities I have gathered during my internship period at Lembaga Pelabuhan Johor (LPJ) for 24 weeks. The period of my internship started from September 1, 2023 until February 9, 2024. During that period, some experienced and memories will be share in this report. The first section will be the basic introduction of report including the executive summary. Next is about the student’s profile which I will share my resume in this section. Continue with company’s profile which I will explain more about company’s background, vision, mission and objectives. Also, organizational chart of Lembaga Pelabuhan Johor will be included in this section. In the fourth section, I will share my experience in training reflection section. Here I may share the experience and memories that I gained during my internship in Lembaga Pelabuhan Johor. Next section is about SWOT & PESTLE analysis. Some explanation about SWOT & PESTLE analysis will be discussed here.